Konsep Dan Gagasan Pemenuhan Perlindungan Hak Anak Oleh Pemerintah Daerah Di Perbatasan NKRI - Laurensius Arliman S (Jurnal Selat, 2015)
Indonesia is a vast archipelago country and borders directly with other countries. This article will look at the role of local government borders on child protection. The author will explain the rights of children to education and health. This paper also discusses how the role of local government borders on child protection, as well as offering ideas on child protection by the border area. The conclusion of this paper, the role of border areas are still lacking in meeting the protection of children, this is due to lack of support from the central government. Key words: Concept; Nation; Child Protection; Border Area.